2007
DOI: 10.4278/0890-1171-22.2.114
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Stair Climbing: Intervention Effects Generalize to a Subsequent Stair Ascent

Abstract: PurposeStudies report a significant increase in stair use when message prompts are introduced at the 'point-of-choice' between stairs and escalators. Climbing one set of stairs, however, will not confer meaningful health dividends. Therefore, this study examined whether exposure to point-of-choice prompts also encourages individuals to climb the next set of stairs that they encounter. DesignInterrupted time-series design. SettingsTwo separate stair/escalator pairings within a UK shopping mall (the 'interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 39 publications
1
56
0
Order By: Relevance
“…"; line 2, "Stair climbing burns more"; line 3, "calories per minute than jogging. ", line 4, "Burn some today", a message used successfully in a previous study in a shopping mall (Webb & Eves, 2007). The study was approved by the Ethics Subcommittee of the School of Sport and Exercise Sciences.…”
Section: Methodsmentioning
confidence: 99%
“…"; line 2, "Stair climbing burns more"; line 3, "calories per minute than jogging. ", line 4, "Burn some today", a message used successfully in a previous study in a shopping mall (Webb & Eves, 2007). The study was approved by the Ethics Subcommittee of the School of Sport and Exercise Sciences.…”
Section: Methodsmentioning
confidence: 99%
“…They include demographics (Andersen et al, 1999;Blamey et al, 1995;Brownell et al, 1980;Bungum et al, 2007;Eves et al, 2006;Grimstvedt et al, 2010;Lewis and Eves, 2011;Webb and Eves, 2007); spatial characteristics (e.g. stairwell height [Webb and Eves, 2007]); 'pedestrian volume' (Lewis and Eves, 2011;Webb and Eves, 2007); 'behavioural' context (e.g. leisure/commuter) and presence of stair climbing 'models' (Adams et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Public-access interventions featuring follow-up phases also add little certainty regarding residual effects. Three months after prompts were removed Blamey et al (1995) and Webb and Eves (2007) observed a decline in stair choice, whilst Brownell et al (1980) observed complete reversion to baseline levels. These interventions may have been too short (≤13 weeks) to establish lasting effects.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations